Pelaksanaan Lelang Melalui Internet Terhadap Aset Barang Milik Negara Pada Kantor Pelayanan Kekayaan Negara dan Lelang Serang Berdasarkan Asas Kepastian Hukum - Mafita Mafita (Nurani Hukum, 2019)
This research entitled "Implementation of Auction Through Internet Against State Property Assets at the State Assets and Auction Service Office (KPKNL) Serang Based on the Principle of Legal Certainty. The background of this writing is that the implementation of an auction through the internet specifically regulated in PMK Number 90 / PMK.06 / 2016 concerning Guidelines for Implementing Auctions with Written Offers without Attendance of Bidders Through the Internet, has not fully accommodated internet auction transactions especially for auction of Property Country. The purpose of this paper is to find out and analyze the principle of legal certainty and the form of legal protection for auction buyers in the implementation of an auction through the internet on assets of State Property in the Serang KPKNL. This research is normative legal research, so the approach used is the approach to legislation. Data obtained from literature is accompanied by field studies, namely interviews, and analyzed qualitatively descriptive. The results of this study indicate that the implementation of the auction through the internet still does not meet the principle of legal certainty, because the legal certainty of the implementation of the auction through the internet is only found in auction procedures while the certainty of the truth of the auction object is not fully regulated in the regulation. Legal protection for auction buyers in the implementation of an auction through the internet on BMN assets at Serang KPKNL has not been fully provided, there are still rights from several auction buyers that are not fully fulfilled, namely receiving all auctioned goods / object purchased in accordance with the existing auction announcement.Penelitian ini berjudul “Pelaksanaan Lelang Melalui Internet Terhadap Aset Barang Milik Negara pada Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) Serang Berdasarkan Asas Kepastian Hukum. Latar belakang penulisan ini adalah pelaksanaan lelang melalui internet yang diatur secara khusus dalam PMK Nomor 90/PMK.06/2016 tentang Pedoman Pelaksanaan Lelang dengan Penawaran Secara Tertulis Tanpa Kehadiran Peserta Lelang Melalui Internet, belum sepenuhnya mengakomodir transaksi lelang melalui internet khususnya untuk lelang Barang Milik Negara. Tujuan dari penulisan ini adalah untuk mengetahui dan menganalisis asas kepastian hukum dan bentuk perlindungan hukum bagi pembeli lelang dalam pelaksanaan lelang melalui internet terhadap aset Barang Milik Negara pada KPKNL Serang. Penelitian ini adalah penelitian hukum normatif, maka pendekatan yang digunakan adalah pendekatan peraturan perundang-undangan. Data yang diperoleh dari studi pustaka disertai dengan studi lapangan yaitu wawancara, dan dianalisis secara kualitatif deskriptif. Hasil penelitian ini menunjukan bahwa pelaksanaan lelang melalui internet masih belum memenuhi asas kepastian hukum, karena kepastian hukum pelaksanaan lelang melalui internet hanya terdapat dalam prosedur lelang sedangkan adanya kepastian kebenaran objek lelang belum sepenuhnya diatur dalam peraturan tersebut. Perlindungan hukum bagi pembeli lelang dalam pelaksanaan lelang melalui internet terhadap aset BMN pada KPKNL Serang belum sepenuhnya diberikan, masih terdapat hak dari beberapa pembeli lelang yang tidak seluruhnya terpenuhi, yaitu menerima seluruh barang/objek lelang yang dibelinya sesuai dengan pengumuman lelang yang ada.